Efficacy and safety of mammalian target of rapamycin inhibitors following intestinal and multivisceral transplantation. Issue 7 (22nd June 2021) - Modi, Krishna; Segovia, Maria; Mavis, Alisha; Schiano, Thomas; Patel, Yuval; Boike, Justin; Sudan, Debra; Nagai, Shunji; Jafri, Syed‐Mohammed
Abstract: This is a descriptive study reviewing the outcomes of mammalian target of rapamycin inhibitors (mTORs) in intestinal (IT) and multivisceral transplantation (MVT). This study included 22 patients, 20 adults, and two children, and an overall mean age of 46 years old at the time of transplantation. Twelve patients (54.5%) received IT, and the remainder (45.5%) MVT. The mean time between transplantation and mTORs initiation was 24 months. The indication was worsening renal function in 13 patients (59%), with 9/13 (69.2%) noted to have an increase in glomerular filtration rate of at least 10 ml/min/1.73m 2 . The indication for four patients (18.2%) was a history of neuroendocrine tumor. After mTOR initiation, 50% of patients were reduced or weaned off tacrolimus and 13.7% off prednisone. mTORs were discontinued in 11/22 patients. Six patients (54.5%) stopped due to side effects, two (18.1%) for surgery, and one (9%) for acute cellular rejection. Side effects were edema (33.3%), headaches (33.3%), diarrhea (16.7%), and oral ulcers (16.7%). The average duration of mTORs prior to discontinuation due to side effects was 7 months. mTORs may function in their own niche of patients due to the potential renal safety profile, but use is most limited by tolerance to side effects.